2020
DOI: 10.7554/elife.53350
|View full text |Cite
|
Sign up to set email alerts
|

The natverse, a versatile toolbox for combining and analysing neuroanatomical data

Abstract: To analyse neuron data at scale, neuroscientists expend substantial effort reading documentation, installing dependencies and moving between analysis and visualisation environments. To facilitate this, we have developed a suite of interoperable open-source R packages called the <monospace>natverse</monospace>. The <monospace>natverse</monospace> allows users to read local and remote data, perform popular analyses including visualisation and clustering and graph-theoretic analysis of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 143 publications
(271 reference statements)
1
174
0
Order By: Relevance
“…We also grouped vTel y321 neurons using NBLAST hierarchical clustering methods applied to zebrafish forebrain neurons in a previous study, which yielded similar results (data not shown). 44,45 Complex arbors remain over-represented in 14 dpf XGF larvae relative to their CVZ siblings ( Figure 4c, d: aqua, purple). Therefore, it appears that the majority of vTel y321 neurons analyzed in GF or XGF fish are morphologically similar to those from CVZ siblings, but that the microbiota normally restrains arborization of a subset of vTel y321 neurons that become dramatically more complex in GF or XGF conditions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We also grouped vTel y321 neurons using NBLAST hierarchical clustering methods applied to zebrafish forebrain neurons in a previous study, which yielded similar results (data not shown). 44,45 Complex arbors remain over-represented in 14 dpf XGF larvae relative to their CVZ siblings ( Figure 4c, d: aqua, purple). Therefore, it appears that the majority of vTel y321 neurons analyzed in GF or XGF fish are morphologically similar to those from CVZ siblings, but that the microbiota normally restrains arborization of a subset of vTel y321 neurons that become dramatically more complex in GF or XGF conditions.…”
Section: Resultsmentioning
confidence: 97%
“…This generated transformed images and image rotation, translation, scaling, shearing, and centering coordinates used to achieve that transformation. These transformation coordinates were then applied to SWC-formatted neurons using Natverse package functions in R. 45 Formatting neurons as SWC files converts them into a matrix of (x,y,z) coordinates so that they can be read across platforms. For each condition, transformed neurons were exported from R in SWC format and imported into the average vTel y321 GFP forebrain for 3D visualization in Imaris software (Oxford Instruments, Concord MA).…”
Section: Image Analysis Neuronal Morphology Was Extracted From Confomentioning
confidence: 99%
“…Similar tools have been developed for other model organisms, such as the Allen Mouse Brain Connectivity Atlas [43], the WormAtlas for C. elegans [3] and the Z Brain for zebra fish [44]. A number of projects, e.g., [5], offer a more specialized capability for visualizing and analyzing neuroanatomy data.…”
Section: Discussionmentioning
confidence: 99%
“…To classify the reconstructed cells into neuronal and other cell types, we used various approaches. For a morphological classification of neurons based on the similarity of their skeleton arbots, we used Sholl analysis (Sholl, 1953) and NBLAST as implemented in CATMAID and the natverse (Bates et al, 2020;Costa et al, 2016), respectively. Hierarchical clustering of distance matrices obtained from NBLAST and Sholl analysis often delineated neurons with similar arbors that we consider cell types (shown for the motoneurons in Figure 3 -figure supplement 1).…”
Section: Classification Of Cell Typesmentioning
confidence: 99%
“…NBLAST was carried out in the natverse (Bates et al, 2020;Costa et al, 2016) by a custom R script. We compared 1,772 neurons in the connectome (annotated: "connectome_neuron").…”
Section: Network Analysis Nblast and Sholl Analysismentioning
confidence: 99%